An edition, translation and commentary of chapters 6th, 7th and 8th of Qutb al-Din al-Shirazi's Nihayat al-idrak fi dirayat al-aflak - Norzakiah binti Saparmin (International Islamic University Malaysia, International Institute of Islamic Thought and Civilization, 2008)
The dissertation is an edition, translation and commentary of the three important chapters in the work of a well-known Muslim philosopher and astronomer Qutb al-Din al-Shirazi (d. 1311 C.E.). The text, known as Nihayat al-Idrak fi Dirayat al-Aflak (The Limit of Understanding of the Knowledge of the Heavens), is one of his few major works on astronomy. For the purpose of this study, we focused only on the three important chapters, which are “On the Orbs and Motions of the Sun,” “On the Orbs and Longitudinal and Latitudinal Motions of the Moon,” and “On the Orbs and Longitudinal Motions of the Upper Planets and Venus.” These celestial objects, and if we include Mercury and the fixed stars as well, are the only known and observable object of the sky which are being observed and studied by the medieval astronomers. Moreover, it is in these three chapters lies the originality of the work of Qutb al-Din al-Shirazi, and his famous predecessors, Nasir al-Din al-Tusi (d. 1274 C.E.) and Mu'ayyad al-Din al-'Urdi (d. 1266 C.E>.). They are the prominent members of the “Maragha School,” a name which modern scholarship had coined after a group of Muslim medieval astronomers who are the most revolutionist in reforming Ptolemaic astronomy. However, as we shall see in the study, Qutb al-Din al-Shirazi utilized theories of his predecessors, instead of creating his own theory, in composing his Nihayat. His text is more like a commentary for the work of his predecessors. For the purpose of the edition, we used five manuscripts: Ahmet III 3333, Berlin 5682, Paris 2517/8, British Library 399, and Bodleian Marsh 133. It is found that there is no major variation among the manuscripts, and if there is any, it is mentioned accordingly.